A prospective study to determine the clinical utility of pharmacogenetic testing of veterans with treatment-resistant depression. (August 2021) - McCarthy, Michael J; Chen, Yucui; Demodena, Anna; Leckband, Susan G; Fischer, Eileen; Golshan, Shahrokh; Suppes, Trisha; Kelsoe, John R
Background: Pharmacotherapies for depression are often ineffective and treatment-resistant depression (TRD) is common across bipolar disorder (BD), major depressive disorder (MDD), and post-traumatic stress disorder (PTSD). Patient genetic information can be used to predict treatment outcomes. Prospective studies indicate that pharmacogenetic (PGX) tests have utility in the treatment of depression. However, few studies have examined the utility of PGX in other diagnoses typified by depression, or in veterans, a cohort with high rates of medical comorbidity, social stress, and suicide. Aim: To determine the efficacy of genetically guided pharmacological treatment of TRD. Methods: We conducted an 8-week, prospective, multisite, single-blind study in 182 veterans with TRD including patients with BD, MDD, and PTSD. Subjects were randomly assigned to PGX-guided treatment in which the clinician incorporated PGX information into decision-making, or treatment as usual (TAU). Results: Overall, the PGX group improved marginally faster compared to TAU, but the difference was not statistically significant. Secondary analyses revealed that only PTSD patients showed a potential benefit from PGX testing. Patients predicted by PGX testing to have moderate levels of genetic risk showed a significant benefit from the PGX-guided treatment, whereas other risk groups demonstrated no benefit. Clinicians generally found the PGX test was useful, particularly in more depressed patients and/or those with more warnings for significant or serious adverse outcomes. Clinicians more often used the results to select a drug, but only rarely to adjust dosing. Conclusions: The data reveal possible group differences in the utility of PGX testing in veterans with TRD. ClinicalTrials.gov Identifier: NCT04469322.